PROCAL: A Set of 40 Peptide Standards for Retention Time Indexing, Column Performance Monitoring, and Collision Energy Calibration. Issue 21 (24th October 2017) - Zolg, Daniel Paul; Wilhelm, Mathias; Yu, Peng; Knaute, Tobias; Zerweck, Johannes; Wenschuh, Holger; Reimer, Ulf; Schnatbaum, Karsten; Kuster, Bernhard
Abstract: Beyond specific applications, such as the relative or absolute quantification of peptides in targeted proteomic experiments, synthetic spike‐in peptides are not yet systematically used as internal standards in bottom‐up proteomics. A number of retention time standards have been reported that enable chromatographic aligning of multiple LC–MS/MS experiments. However, only few peptides are typically included in such sets limiting the analytical parameters that can be monitored. Here, we describe PROCAL (ProteomeTools Calibration Standard), a set of 40 synthetic peptides that span the entire hydrophobicity range of tryptic digests, enabling not only accurate determination of retention time indices but also monitoring of chromatographic separation performance over time. The fragmentation characteristics of the peptides can also be used to calibrate and compare collision energies between mass spectrometers. The sequences of all selected peptides do not occur in any natural protein, thus eliminating the need for stable isotope labeling. We anticipate that this set of peptides will be useful for multiple purposes in individual laboratories but also aiding the transfer of data acquisition and analysis methods between laboratories, notably the use of spectral libraries.